Análise genômica comparativa de linhagens de Staphylococcus aureus isoladas de diferentes formas de mastite em ovinos - Ana Carolina Barbosa Caetano (2018)
Staphylococcus aureus is the major etiological agent of mastitis in small ruminants, worldwide. Mastitis is a mammary gland inflammation that is difficult to cure and prone to resurgence, leading to great economical losses in milk production and herd animals. To date, little is known about the genomic features specific to S. aureus strains isolated from mastitis in small ruminants, such as ovines. The study of the genomes of these microorganisms might contribute to a better understanding of the bacterial traits involved in the host specialization, supporting the development of new treatment and control strategies for ovine mastitis. In this study, comparative genomic analyses between 12 strains isolated from ovine mastitis in France and 11 genomes, isolated from various hosts, retrieved from the NCBI database, were performed. Results revealed 3,964 different genes found in the genomes and 2,969 genes shared between the groups, out of these, 859 are accessory genes. The 2,110 genes, which comprise the core genome, are involved in the cellular metabolism, according to the COG distribution analysis. Beyond the cellular metabolism category, the groups of accessory genes and genes exclusively found in the ovine strains include the cell signaling category. Prophages, pathogenicity and genomic island were predicted and carries important bacterial virulence factors. A cluster of ovine strains was formed in the Average Nucleotide Identity analysis. Besides that, the Multilocus Sequence Typing analysis revealed two big clonal- related group of S. aureus ovine, except for three strains that can be considered atypical. This result is in agreement with the phylogenetic analysis. In addition, some sheep and cattle strains can be evolutionary related. These comparative genomic analyses may contribute to the identification of traits acquired through lateral gene transfer, as well as the roles of these traits in host adaptation and virulence, and characterization of S. aureus ovine strains.